Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1177/0013916594261006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Hazards, Health, and Racial Inequity in Hazardous Waste Distribution

Abstract: This study addresses the critical issue of hazardous wastes and associated human health problems. The issue of inequitable distribution of environmental hazards by race is discussed with special reference to a municipal solid waste landfill and the petrochemical plants as the principal environmental stressors in the Baton Rouge Standard Metropolitan Statistical Area (SMSA). In a random sample of 213 respondents, the majority considered toxic wastes as a major threat to human health. Other findings indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 16 publications
8
42
1
Order By: Relevance
“…The results showed the same pattern for environmental experiences and health threats. In fact, despite the strong evidence suggesting inequalities in relation to the exposure to certain environmental events 12,13,14,15 , our results show that there is not a clear acknowledgement of that among our sample. This result is extremely interesting, as environmental threats can have very concrete expressions (dust, dirty water, etc.…”
Section: Richcontrasting
confidence: 97%
See 1 more Smart Citation
“…The results showed the same pattern for environmental experiences and health threats. In fact, despite the strong evidence suggesting inequalities in relation to the exposure to certain environmental events 12,13,14,15 , our results show that there is not a clear acknowledgement of that among our sample. This result is extremely interesting, as environmental threats can have very concrete expressions (dust, dirty water, etc.…”
Section: Richcontrasting
confidence: 97%
“…Evidence suggests that poor people, from underprivileged minorities, are the ones who mostly end up living in the most industrialized and polluted places 11,12,13,14,15 . For instance, a recent study conducted in England 16 showed an unequal distribution of industrial sites, with these installations disproportionately located in deprived areas and near deprived populations.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with other studies that have examined public concerns surrounding the remediation of contaminated sites (3,14,21). The high rating given to public involvement, moreover, appears consistent with the findings of recent studies that contend that the public perceives many of the gravest threats to health and environmental well-being as attributable to a lack of political accountability, a need for direct citizen activism, and a high degree of distrust toward authorities perceived to be responsible for environmental hazards (14,22 bViewed as minimal concern as determined by percentage of respondents choosing 1 or 2 on a 1-5 rating scale.…”
Section: Site Concernssupporting
confidence: 92%
“…3;2014 livestock, environmental pollutions, and an increasing number of incidents that have caused ill-health and epidemic of diseases like malaria and respiratory diseases. A potentially more serious risk to human health is the contamination of source of water supply (Adeola, 1996).…”
Section: Introductionmentioning
confidence: 99%